2018
DOI: 10.1590/2358-2936e2018008
|View full text |Cite
|
Sign up to set email alerts
|

Color patterns of the hermit crab Calcinus tibicen (Herbst, 1791) fail to indicate high genetic variation within COI gene

Abstract: BRAZIlIAn cRUstAceAn socIetY Nauplius, 26: e2018008 orcid.org/0000-0002-8497-187X All content of the journal, except where identi ed, is licensed under a Creative Commons attribution-type BY. Color pa erns of the hermit crab Calcinus tibicen (Herbst, 1791) fail to indicate high genetic variation within COI gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Simone et al coll., 08.x.2012, SCUBA, 0-10 m; 6 males, 1 ovigerous female (29753), Costa Rica, Puerto Viejo, 9°39'28"N, 82°45'20"W, G. Guzmán coll., 13.vii.2013, intertidal; 1 male (MZUSP 13894), Brazil, Pernambuco, Fernando de Noronha, Praia do Meio, Simone & Souza coll., 22.vii.1999; 1 male, 7 ovigerous females (MZUSP 17712), Brazil, Bahia, Abrolhos, W. Narchi coll., ix.1965; 4 males, 3 ovigerous females (MZUSP 7028), Brazil, Bahia, Abrolhos, Ilha Redonda, P. Young coll., 21.i.1985; 1 male (MZUSP 34990), Brazil, Ceará, Fortaleza, Meireles rock beach, Anker & Feitosa coll., 15.vi.2011; 1 ovigerous female (MZUSP 29139), Brazil, Espírito Santo, Piúma, Calcinus tibicen and the eastern Atlantic C. talismani A. Milne-Edwards & Bouvier, 1892, superficially resemble each other in having the upper margin of the right chela smooth, and grooved P3 propodus, but can be easily disguished in that the dorsal margin of the P3 propodus is distinctly angulous in C. tibicen, whereas in C. talismani it is rounded (Poupin 2003). Mandai et al (2018a) considered the differences of color pattern among northeastern and southeastern Brazilian specimens of C. tibicen a case of polymorphism and, without further explanation, suggested that it "might be related to the kind of nutrition as well different ecological and evolutionary predation characteristics." Later on, however, Mandai et al (2018b), based on two mitochondrial markers, found that northwestern Atlantic specimens differed from northeastern and southeastern Brazilian coast specimens, despite the lack of morphological evidences to support each genetic group.…”
Section: Calcinus Tibicen (Herbst 1791) (Fig 3a-d)mentioning
confidence: 99%
“…Simone et al coll., 08.x.2012, SCUBA, 0-10 m; 6 males, 1 ovigerous female (29753), Costa Rica, Puerto Viejo, 9°39'28"N, 82°45'20"W, G. Guzmán coll., 13.vii.2013, intertidal; 1 male (MZUSP 13894), Brazil, Pernambuco, Fernando de Noronha, Praia do Meio, Simone & Souza coll., 22.vii.1999; 1 male, 7 ovigerous females (MZUSP 17712), Brazil, Bahia, Abrolhos, W. Narchi coll., ix.1965; 4 males, 3 ovigerous females (MZUSP 7028), Brazil, Bahia, Abrolhos, Ilha Redonda, P. Young coll., 21.i.1985; 1 male (MZUSP 34990), Brazil, Ceará, Fortaleza, Meireles rock beach, Anker & Feitosa coll., 15.vi.2011; 1 ovigerous female (MZUSP 29139), Brazil, Espírito Santo, Piúma, Calcinus tibicen and the eastern Atlantic C. talismani A. Milne-Edwards & Bouvier, 1892, superficially resemble each other in having the upper margin of the right chela smooth, and grooved P3 propodus, but can be easily disguished in that the dorsal margin of the P3 propodus is distinctly angulous in C. tibicen, whereas in C. talismani it is rounded (Poupin 2003). Mandai et al (2018a) considered the differences of color pattern among northeastern and southeastern Brazilian specimens of C. tibicen a case of polymorphism and, without further explanation, suggested that it "might be related to the kind of nutrition as well different ecological and evolutionary predation characteristics." Later on, however, Mandai et al (2018b), based on two mitochondrial markers, found that northwestern Atlantic specimens differed from northeastern and southeastern Brazilian coast specimens, despite the lack of morphological evidences to support each genetic group.…”
Section: Calcinus Tibicen (Herbst 1791) (Fig 3a-d)mentioning
confidence: 99%
“…Despite the attention that this biological trait has received in some crustaceans (e.g. Bauer 2004, Martin andZimmerman 2007), the available literature addressing colour descriptions on hermit crabs has focused mainly on genera involving very striking species such as Calcinus (Pessani and Tirelli 2006, Malay and Paulay 2010, Mandai et al 2018, Ciliopagurus Lemaitre 2003, Poupin andMalay 2009), Clibanarius (Negri et al 2014), Paguropsis (Lemaitre et al 2018) and Cancellus (Felder and Lemaitre 2020), all of them with a greater number of species in tropical latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Although colour patterns do not always reflect genetic differences (Mandai et al 2018), they can reveal an ongoing evolutionary process through which two or more species diverged from a common ancestor, the colour sometimes being the only discernible difference between them (Udekem d'Acoz 1995, Poupin and Malay 2009). An example among the species found in our study area is the case of Clibanarius aequabilis (Dana, 1851), found in the Macaronesian islands and genetically different from Clibanarius erythropus (Latreille, 1818), which is present in waters off the Iberian Peninsula (Almón et al in prep.).…”
Section: Introductionmentioning
confidence: 99%
“…Key literature (Provenzano 1959;McLaughlin & Provenzano 1974;Strasser & Price 1999), and extensive photographic evidence compiled by us document variation in color among individuals otherwise assignable by current definition as P. tortugae. Although these differences have long been observed, they have historically been regarded as ecomorphic variations of the phenotype closely tied to habitat substrate color (McLaughlin & Provenzano 1974), which could indeed apply to some paguroid taxa (Mandai et al 2018).…”
Section: Introductionmentioning
confidence: 99%